Duplication of the Gallbladder as an Operative Surprise: A Case Report with Review of the Literature. (12th February 2021) - Singh, Jai P.
Abstract : Introduction . Duplication of the gallbladder is a rare congenital anomaly of the biliary system. Anomalous anatomy of the biliary system is associated with an increased risk of complications such as bile duct injury during cholecystectomy. Herein, I present a case report of duplication of the gallbladder, which was an operative surprise as the patient's preoperative workup did not reveal any evidence of duplication of the gallbladder. Case Report . A 60-year-old female was admitted for management of recurrent pancreatitis. Diagnosis of biliary pancreatitis was made as her CT and US revealed cholelithiasis. During laparoscopic cholecystectomy, she was found to have duplication of the gallbladder, which was a surgical surprise. Both the gallbladders were successfully removed, and the patient had an uneventful postoperative course. Conclusion . Duplication of the gallbladder is a rare congenital anomaly, which could be associated with other congenital anomalies of the bile duct and vascular system. Extreme care should be taken during cholecystectomy as these anomalies could lead to serious injury to the bile duct and vessels.